Climate Savvy Adapting Conservation and Resource Management to a Changing World - Hansen, Lara J.; Hoffman, Jennifer R. (Island Press/Center for Resource Economics : Imprint: Island Press, 2011)
Climate change demands a change in how we envision, prioritize, and implement conservation and management of natural resources. Addressing threats posed by climate change cannot be simply an afterthought or an addendum, but must be integrated into the very framework of how we conceive of and conduct conservation and management.   In Climate Savvy, climate change experts Lara Hansen and Jennifer Hoffman offer 18 chapters that consider the implications of climate change for key resource management issues of our time-invasive species, corridors and connectivity, ecological restoration, pollution, and many others. How will strategies need to change to facilitate adaptation to a new climate regime? What steps can we take to promote resilience?   Based on collaboration with a wide range of scientists, conservation leaders, and practitioners, the authors present general ideas as well as practical steps and strategies that can help cope with this new reality.   While climate change poses real threats, it also provides a chance for creative new thinking. Climate Savvy offers a wide-ranging exploration of how scientists, managers, and policymakers can use the challenge of climate change as an opportunity to build a more holistic and effective philosophy that embraces the inherent uncertainty and variability of the natural world to work toward a more robust future.